ATP- and Adenosine-Mediated Signaling in the Central Nervous System: Adenosine Stimulates Glutamate Release From Astrocytes via A2a Adenosine Receptors - Tomoyuki Nishizaki (Elsevier, 2004)
Adenosine enhanced intracellular Ca2+ concentrations in astrocytes via A2a adenosine receptors involving protein kinase A (PKA) activation. The Ca2+ rise is inhibited by brefeldin A, an inhibitor of vesicular transport; but not by neomycin and U73122, phospholipase C inhibitors; xestospongin, an IP3-receptor inhibitor; ryanodine, a ryanodine-receptor inhibitor; TMB-8, an endoplasmic reticulum calcium-release blocker; octanol, a gap-junction inhibitor; or cadmium, a non-selective, calcium-channel blocker. Adenosine stimulates astrocytic glutamate release via an A2a adenosine receptors/PKA pathway, and the release is inhibited by the vesicular transport inhibitors brefeldin A and bafilomycin A1. A2a adenosine receptors and the ensuing PKA events, thus, are endowed with vesicular Ca2+ release from an unknown intracellular calcium store and vesicular glutamate release from astrocytes. Keywords:: adenosine, A2a receptor, glutamate release, Ca2+, astrocyte